THE ROLE OF MARKETING STRATEGY ON PRICING AND ITS IMPACT ON PURCHASING INTEREST - Utami, Cut Vania; Karunia, Luki; Marwan, Jubery; Franky (Moestopo International Review on Social, Humanities, and Sciences, 2024)
This research aims to analyze and statistically test the role of marketing strategy on pricing and its impact on purchasing interest. This research was conducted at Cafe Covare Graha PPI using a survey method and analyzed using the Partial Least Square Structural Equation Modeling method. The total sample was 196 respondents who were chosen randomly. The analysis results show that; 1) Marketing strategy significantly influences pricing, 2) Marketing strategy does not have a significant influence on service quality, 3) Marketing strategies do not have a significant influence on consumer buying interest, 4) Pricing has a significant influence on purchase interest. Competitive prices that align with the value perceived by consumers can significantly increase purchasing interest. 5) Service quality does not have a significant influence on purchasing interest, 6) Marketing strategy has a significant effect on purchasing interest through pricing. Good pricing can bridge the influence of marketing strategy on consumer buying interest. 7) Marketing strategy does not significantly affect buying interest through service quality. This indicates that service quality is not a strong mediating factor in the relationship between marketing strategy and purchase intention.